Imprint cytology: a useful screening test for diagnosis of Helicobacter pylori in resource poor settings - Arachchi, Piyumali Sandareka (BMC Res Notes, 2018)
OBJECTIVE: The study aimed to compare the usefulness of two staining methods for imprint cytology for diagnosis of Helicobacter pylori infection. Gastric biopsy specimens (from dyspeptic patients attending routine upper gastrointestinal endoscopy) were placed on glass slides to obtain imprints. The imprints were stained with Toluidine blue and Giemsa stains separately and observed under ×400 magnification using a light microscope. Imprinted biopsies were sectioned and stained with H & E stain and Giemsa stain for histological analysis. Diagnosis of H. pylori infection in both imprint and histological sections were confirmed by a consultant pathologist. The sensitivity, specificity, positive predictive value and negative predictive value of each stain were calculated and benchmarked against histological diagnosis. RESULTS: Of the 55 dyspeptic patients enrolled in the study, 5 were positive for H. pylori by Toluidine blue stain and 4 by Giemsa stain. The sensitivity of Toluidine blue stain (57.1%) was higher than Giemsa stain (42.9%) while the specificity of both stains was equal (97.9%). Giemsa stain gave a better discrimination for identification of H. pylori bacteria among the mucosal background. Imprint cytology is a rapid, simple and cost effective diagnosis method that can supplement histological diagnosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13104-018-3592-2) contains supplementary material, which is available to authorized users.